MyD88 signalling is critical in the development of pancreatic cancer cachexia. Issue 2 (21st January 2019) - Zhu, Xinxia; Burfeind, Kevin G.; Michaelis, Katherine A.; Braun, Theodore P.; Olson, Brennan; Pelz, Katherine R.; Morgan, Terry K.; Marks, Daniel L.
Abstract: Background: Up to 80% of pancreatic cancer patients suffer from cachexia, a devastating condition that exacerbates underlying disease, reduces quality of life, and increases treatment complications and mortality. Tumour‐induced inflammation is linked to this multifactorial wasting syndrome, but mechanisms and effective treatments remain elusive. Myeloid differentiation factor (MyD88), a key component of the innate immune system, plays a pivotal role in directing the inflammatory response to various insults. In this study, we tested whether MyD88 signalling is essential in the development of pancreatic cancer cachexia using a robust mouse tumour model. Methods: Sex, age, and body weight‐matched wide type (WT) and MyD88 knockout (MyD88 KO) mice were orthotopically or intraperitoneally implanted with a pancreatic tumour cell line from a syngeneic C57BL/6 KRAS G12D/+ P53 R172H/+ Pdx‐Cre (KPC) mouse. We observed the effects of MyD88 signalling during pancreatic ductal adenocarcinoma progression and the cachexia development through behavioural, histological, molecular, and survival aspects. Results: Blocking MyD88 signalling greatly ameliorated pancreatic ductal adenocarcinoma‐associated anorexia and fatigue, attenuated lean mass loss, reduced muscle catabolism and atrophy, diminished systemic and central nervous system inflammation, and ultimately improved survival. Our data demonstrate that MyD88 signalling plays a critical role in mediating pancreatic cancer‐induced inflammation that triggers cachexia development and therefore represents a promising therapeutic target. Conclusions: MyD88‐dependent inflammation is crucial in the pathophysiology of pancreatic cancer progression and contributes to high mortality. Our findings implicate the importance of innate immune signalling pathways in pancreatic cancer cachexia and a novel therapeutic target.